Prayer Time Reminder and Mobile Phone Jammer for Mosque Based on Raspberry PI - Wahyu Aulia Nurwicaksana; Septyana Riskitasari; Supriatna Adhisuwignjo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
Prayer time reminder based on raspberry pi with LCD TV as a display that not only can be set according to locationbased on GPS coordinates, but also contain information in the form of picture, text, video, etc. This is much betterthan just simple words placed on dot matrix or running text as it is today. Display design can be fully customized asper needed, it can be accommodated because the system based on raspberry pi mini PC. The method used for thisresearch is by conducting literature studies and field studies that are necessary for system design and manufacture.This system had several components involve include raspberry pi, signal jammer, air freshner, and LCD TV. Thisprayer time reminder display information of mosque name, address, clock, prayer schedule based on GPS coordinate,event photo, announcement, video, and running text as per installed program. This reminder also act as mobile phonesignal jammer, so there is no interference based on mobile phone signal. Jammer activated when entered prayer timeup to at least 30 minutes later. It function can also be added as air freshner which will spray as long as the jammer isactivated at 10 minute intervals.